Unicorn Valuation Model Application: An Analysis of Multinational Internet Companies with ByteDance as an Example - Yao Jiacheng (SHS Web of Conferences)
The rapid development of the internet has led to the rise of multinational internet unicorn companies, attracting significant attention from both domestic and international markets. As a result, identifying an appropriate valuation method has become a critical challenge. However, traditional valuation methods cannot always be used on these companies properly due to their relatively short operational history, limited financial disclosures, and the domination of intangible assets. To solve these problems, this study applies an improved Discounted Equity Value Analysis (DEVA) valuation model, incorporating market penetration rates and industry-related coefficients to enhance the accuracy of valuations. Given that ByteDance currently holds the highest valuation among unicorns worldwide, operates on a global scale, and holds a relatively comprehensive disclosure mechanism, it serves as a highly representative case among unicorns. Consequently, this study selects ByteDance as the research subject, ultimately estimating its valuation in 2023 at $225.3 billion. This figure closely aligns with the $268 billion buyback valuation reported by Sina Finance. Thus, the improved DEVA valuation model provides a new perspective for assessing the valuation of internet unicorn companies.